SERANGGA HAMA TANAMAN GAHARU (Aquilaria spp) DI AREAL AGROFORESTRY DESA NANGA KALAN KABUPATEN MELAWI - Sulistio, Bambang; hanuddin, Bur; Darwati, Herlina (JURNAL HUTAN LESTARI, 2014)
Agroforestry area in the village of Nanga Kalan Ella Hilir Subdistrict Melawi District is an area that is developed from the forest service, these areas are interspersed rubber plant aloes, sengon and mahoni. Gaharu is one of the priority plant because it has a short cycle, does not have a requirement to grow the and have high production values high. Purpose this study to determine the level of damage caused by insects aloe plant and identify the type of insect aloe plant in the village of Nanga Kalan agroforestry area. The results were obtained insect pests that attack plants, consisting of the 4 order Lepidoptera, Coleoptera, Orthoptera, Hemitera, with the 5 Family Lymantriidae, Chrysomeliae, Acrididae, Pentatomidae, Alydidae and 5 Genus is Euproctis, Aulacophora, Valanga, Heteroptera, Leptocorisa. The types of insect pests which attack plants such as aloes : caterpillar fur (Lymantriidae), leaf beetles (Phaedonia inclusa), locust wood (Valanga nigricornis zehnleri), ladybugs plants (Anasa tristis Deger), walang rice pest (Leptocorisa oratorius) . AsÂ  much as 71 rods aloe plant attacked by insect pests of 150 stems of plants were observed, with the percentage of insect pests in the aloe plant is 47.33%, moderate damage category. Damaged parts of the plant are the leaves and the leaves are perforated bud from top to bottom, bite at the edge of the leaf up to the middle, wrinkled leaves and roll, half the leaves disappear and leaves no living bone. Keywords : Pest, plant,gaharu,Nanga Kalan